Stroke-induced Focal Status Epilepticus (Ictus, 2022)
Clinical Imagen presented in issue 3 number 1 of Ictus, Journal of the Mexican Stroke Association.
Keywords: Status Epilepticus; Stroke; Epilepsy; Ischemic Stroke; Neurocritical